Corporate Social Responsibility and Green Accounting: Effects on Profitability During COVID-19 in Indonesia - Laksmi Regita Sari; I Made Pande Dwiana Putra (E-Jurnal Akuntansi, 2026)
The objective of this study is to examine and gather empirical data about the impact of green accounting practices and disclosures regarding social responsibility on industrial firms' profitability in Indonesia during the Covid-19 outbreak. The 189 manufacturing enterprises that were regularly listed on  the  Indonesia  Stock  Exchange  between  2020  and  2022  comprise  the  study's  population.  Purposive sampling  was  used  to identify the research sample, and the results showed that the sample consisted of 45 assessments or 15 enterprises. Multiple linear regression analysis is the method of analysis. The study's findings indicate that while the adoption of green accounting has a favorable impact on profitability, the release of corporate social responsibility has no bearing on it.